‘Unpacking’ young travellers’ needs to enhance the attractiveness of package tours - Ahmad, A.; Izian Idris, *; Mason, C.; Sheikh Khairuddin, S. M. H.; Abdul Menon, A. S.; Shamsudin, M. F.; Masri, R.; Hasim, M. A. (Hampstead Psychological Associates, 2020)
This paper presents the findings of a study which adapts the Travel Need Model established from past literature to gain insights on the three different travel needs which predicted to influence the needs of young travellers towards a package tour namely, travel motives, travel behaviour and travel barriers. Data were collected from 200 respondents (young travellers) and was quantitatively analyzed using SPSS to see the relationship between the three independent variables against the dependent variable. Surprisingly, the results show that all three different travel needs influenced the attractiveness of package tours. It is concluded that having a better understanding of the travel needs of young travellers will enable tour operators in Malaysia to improve and update their package tours to be more attractive simultaneously attract more young travellers to travel with them. This study could enhance the existing literature and give insights to academician, researchers and tour operators.